Economic analysis and resource use efficiency of carrot production in Chitwan district, Nepal - Sapkota, Bina; Tripathi, Kalyani Mishra; Parajuli, Sapana; Gautam, Samikshya; Adhikari, Gaurav; Sharma, Bala; Bhandari, Subash (Journal of Agriculture and Natural Resources, 2020)
A study was conducted from February to May 2020 to analyze the cost-benefit economics analysis and resource use efficiency of carrot production in Chitwan, Nepal. Altogether 70 households producing carrot were selected randomly and surveyed through the pre-tested semi-structured interview-based schedule. Data was entered and coded using SPSS 25 and analyzed using STATA 12.1. The study revealed that the total variable cost per hectare for carrot production was US $1803.1 and a benefit-cost ratio of 1.81 was estimated. Cobb-Douglas production function models the relationship between production output and production inputs . Production function analysis including seven explanatory variables, showed a significant positive effect of seed cost, tractor cost and human labor cost (P<0.01), fertilizer and manure cost (P<0.05) on gross return but herbicide cost, packaging cost, vitamin and micronutrients cost were found insignificant. The return to scale was found to be 1.42. According to estimated allocative efficiency indices, it is suggested to increase the seed, fertilizer and manure, tractor labor and human labor costs by approximately 45%, 74%, 67%, and 79% respectively and reduce the herbicide and packaging costs approximately by 116% and 246% respectively. The adoption of modern technologies with adjustments to resource use should be suggested to maximize the productivity and profit from carrot production.